AKTIVITAS SISWA PADA PENERAPAN PEMBELAJARAN SISTEM PAKEM UNTUK MATA PELAJARAN SAINS - Sudarto, Sudarto (JISOS: JURNAL ILMU SOSIAL, 2023)
This research is a pre-experimental study with a One-Shot Case Study design. Respondents in this study were the 8th Grade of SMPN 3 Makassar in amount of 37 students. The research instrument used is the Observation Sheet. The data collected is data regarding the number of the students who carry out the activities according to the predetermined criteria during the application of the PAKEM system of learning in science subjects. Data analysis uses content and percentage analysis. Data were analyzed using SPSS version 27.0. Result: the student activity during the application of PAKEM learning is to reveal an enthusiastic/enthusiastic and happy mood, to respond actively to the teacher, to carry out learning activities creatively and precisely according to the teacher's directions. Conclusion: during the application of the PAKEM system to te science learning, the students generally carry out positive activities according to the teacher's expectations